Hydroxychloroquine induces inhibition of collagen type II and oligomeric matrix protein COMP expression in chondrocytes (Bangladesh Journal of Pharmacology, 2016)
The aim of this study was to investigate the effect of hydroxychloroquine on the level of collagen type II and oligomeric matrix protein COMP expression in chondrocytes of knee osteoarthritis. The rate of growth in cartilage cells was analyzed using MTT assay whereas the Col-2 and COMP expression levels were detected by RT-PCR and Western blotting analyses. For the determination of MMP-13 expression, ELISA test was used. The results revealed no significant change in the rate of cartilage cell proliferation in hydroxychloroquine-treated compared to untreated cells. Hydroxychloro-quine treatment exhibited concentration- and time-dependent effect on the inhibition of collagen type II and COMP expression in chondrocytes. However, its treatment caused a significant enhancement in the expression levels of MMP-13 compared to the untreated cells. Therefore, hydroxychloro-quine promotes expression of MMP-13 and reduces collagen type II and COMP expression levels in chondrocytes without any significant change in the growth of cells.